Measuring the Effects of Regolith Porosity on Mid-IR Spectra of the Allende Meteorite - Lonnie D. Dausend; Audrey C. Martin; Joshua P. Emery (The Planetary Science Journal)
Mid-infrared (MIR; 5–35 μ m) spectroscopy of laboratory meteorites does not often match asteroid spectra, making it difficult to constrain the parent bodies of meteorites using the MIR. To potentially improve the number of meteorite–asteroid matches, we simulated the effects of regolith porosity on the MIR spectra of the Allende meteorite. We separated a sample of Allende into three particle sizes (<63 μ m) and mixed them with various amounts of potassium bromide (KBr). We then collected MIR spectra of the KBr-mixed Allende samples, defined spectral features that may be indicative of composition and regolith porosity, and analyzed how the parameters of the spectral features (e.g., position and spectral contrast) changed with increasing regolith porosity. The Allende spectra show a transition from surface scattering to volume scattering as regolith porosity increases. Comparing to an olivine sample analyzed the same way shows that the opaque minerals in Allende may not have a significant effect on regolith porosity in the MIR. Finally, we present the MIR spectral analysis of four asteroids measured from the Spitzer Space Telescope: (114) Kassandra, (234) Barbara, (5261) Eureka, and (85989) 1999 JD _6 . We find that Kassandra and Barbara have high total porosities with some evidence of olivine, and Eureka and 1999 JD _6 have low total porosities, with Eureka having strong evidence of olivine and 1999 JD _6 having little evidence of olivine. This work shows how measuring MIR spectra of KBr-diluted particulate meteorites improves our ability to interpret the surface compositions and regoliths of asteroids from telescopic MIR spectra.